Деякі аспекти протидія російській дезінформації у вітчизняному та міжнародному інформаційному просторах - Кравчук, Анатолій Іванович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Russia all time, during the existence, carries out informative influence on Ukraine. a purpose of these informative operations is elimination of Ukrainian mentality, culture and traditions. And presently, during great aggression, Russia continues the native policy of grab. Policy of elimination and total lie, where plays the not last role – disinformation. Secretary RNBO Ukraine Oleksij Danilov came forward at international conference on a theme “Counteraction of disinformation in the conditions of military operations” and marked that Russian propaganda worked similarly as propaganda of nazi Germany worked once. It constantly diffuses a “lie, lie and once again lie” for the whole world, inlaying the milliards of dollars in informative war. If not to resist Russian propaganda, it will lay hands on the mind of many people in Europe and America, creating the threat of them peaceful existence.